Interactive Process Quality Improvement - Marcellus, Richard L.; Dada, Maqbool (Management Science, 1991)
An ongoing production process produces defective parts at random intervals. Each defective part provides a learning opportunity which the decision maker may use to improve the process by investing resources to identify and remove the causes of the defective. For various cost criteria, it is optimal to invest in learning until the probability of producing a defective becomes sufficiently small. This policy has economic interpretations in terms of marginal benefits. In addition, the optimal policy for expected discounted present cost has an interpretation in terms of tradeoffs between “cost of failure” and “cost of prevention”. The shape of the tradeoff curve gives insight into the controversy between the traditional and zero defects views towards cost of quality.